2013
DOI: 10.1186/2045-8118-10-25
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the transcriptome of the rat choroid plexus in relation to neuroprotection

Abstract: BackgroundThe choroid plexuses are the interface between the blood and the cerebrospinal fluid (CSF) contained within the ventricular spaces of the central nervous system. The tight junctions linking adjacent cells of the choroidal epithelium create a physical barrier to paracellular movement of molecules. Multispecific efflux transporters as well as drug-metabolizing and antioxidant enzymes functioning in these cells contribute to a metabolic barrier. These barrier properties reflect a neuroprotective functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 94 publications
(164 reference statements)
11
82
1
Order By: Relevance
“…This is in line with an early maturation of the choroid plexuses during development and suggests that the BCSFB plays a predominant role in brain protection in the neonate and young infant [73,150].…”
Section: Pro-oxidant Speciesmentioning
confidence: 54%
See 1 more Smart Citation
“…This is in line with an early maturation of the choroid plexuses during development and suggests that the BCSFB plays a predominant role in brain protection in the neonate and young infant [73,150].…”
Section: Pro-oxidant Speciesmentioning
confidence: 54%
“…Further protection is provided by antioxidant enzymes (catalase, superoxide dismutase SOD, glutathione peroxidases GPx) and by epoxide hydrolase, which inactivate reactive oxygen species and reactive pro-oxidant epoxides, respectively ◂ depresses ABCC1 levels, which may actually potentiate bilirubin neurotoxicity [45]. Of importance, cytoprotective transporters and enzymes are under the transcriptional regulation of nuclear factors, which are expressed in the choroid plexuses [73]. The nuclear factor erythroid 2-related factor 2 pathway, in particular, represents an attractive target to protect the BCSFB and induce its antioxidant capacities in neurological disorders associated with oxidative stress [168].…”
Section: Pro-oxidant Speciesmentioning
confidence: 99%
“…In a recent study, mmp9 was suggested to lead to Cldn5 degradation at the BCSFB allowing for leukocytes entry into the CSF (Chiu and Lai, 2013). mmp9 is also said to be up-regulated in the CP in the presence of inflammation (Kratzer et al, 2013). We observed a significant increase in mmp9 expression in cp27.5 mutants; however, whether up-regulation is specific to the BCSFB requires further investigation.…”
Section: Rna-seq Analysis Identifies Up-regulated Claudin 5a and Matrcontrasting
confidence: 41%
“…Pleiotropy is where a mutation in one gene can cause multiple phenotypes (Lobo, 2008) Recent discoveries have shed light on the importance of the CP and its contribution to disease. For example, transcriptome analysis during early development revealed that the CP expresses numerous genes essential for CP function, including those for tight junctions, transporters, and metabolic function (Liddelow et al, 2012), protecting the brain from potentially harmful insults (Kratzer et al, 2013). The mutants identified in our study will be used to identify genes essential for maintaining epithelial barrier integrity as well as genes essential for initial barrier formation.…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters characteristic to BBB endothelial cells (ABCB1/ MDR1/P-gp, ABCG2/BCRP, ABCA2, and ABCA8) were included in cluster 5, while members of the ABCC family expressed both by brain endothelial cells and epithelial cells of the choroid plexus (19,40) appeared in clusters 1-3. The main SLC transporters of the BBB were clustered in clusters 1, 2, and 4.…”
Section: Resultsmentioning
confidence: 98%